2001
DOI: 10.1046/j.0953-816x.2001.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Purkinje cells by fluorescence‐activated cell sorting from transgenic mice that express green fluorescent protein

Abstract: The cerebellar Purkinje cell has been the focus of numerous studies involving the analysis of development and information processing in the nervous system. Purkinje cells represent less than 0.1% of the total cell content of the cerebellum. To facilitate studies of molecules that are expressed in such a small proportion of neurons, we have established procedures for the purification of these cells. Transgenic mice were developed in which the expression of green fluorescent protein (GFP) was controlled by the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 23 publications
2
83
0
Order By: Relevance
“…Cones do not express PMCA2, suggesting the cone pathway is dominated by the less sensitive PMCA1 mechanism (Križaj et al, 2002;Haverkamp et al, 2003). A subset of GFP-negative INL cells in retinas from L7-GFP transgenic mice was immunoreactive for PMCA2, indicating that PMCA2 could be localized to cone bipolar cells (Tomomura et al, 2001). However, our observation that photopic ERG is unaffected in PMCA2-deficient mice, together with lack of PMCA2 expression in cones, suggests that this isoform does not play a major role in the cone pathway.…”
Section: Pmca2 Modulates Synaptic Transmission At Rod Synapsesmentioning
confidence: 98%
See 1 more Smart Citation
“…Cones do not express PMCA2, suggesting the cone pathway is dominated by the less sensitive PMCA1 mechanism (Križaj et al, 2002;Haverkamp et al, 2003). A subset of GFP-negative INL cells in retinas from L7-GFP transgenic mice was immunoreactive for PMCA2, indicating that PMCA2 could be localized to cone bipolar cells (Tomomura et al, 2001). However, our observation that photopic ERG is unaffected in PMCA2-deficient mice, together with lack of PMCA2 expression in cones, suggests that this isoform does not play a major role in the cone pathway.…”
Section: Pmca2 Modulates Synaptic Transmission At Rod Synapsesmentioning
confidence: 98%
“…4C,D). Immunostaining of retinas from transgenic mice that express high levels of GFP in rod bipolar cells (Tomomura et al, 2001) additionally suggested postsynaptic localization of PMCA2 to rod bipolar cells (Fig. 4C, arrowheads).…”
Section: Pmca2 Is Abundant In the Retina But Is Not Required For Normmentioning
confidence: 99%
“…To confirm this, we used transgenic mice expressing EGFP under a Purkinje cell-specific promoter, Pcp2 (25). We FACS-sorted their EGFP-positive Purkinje neurons from other cell types in a cerebellar suspension (25) and Western blotted both populations for P-Rex2 expression. Indeed, P-Rex2 protein was found specifically in Purkinje cells (Fig.…”
Section: P-rex2mentioning
confidence: 99%
“…GFP transgenic animals can also be used to mark cell types of interest to be purified by fluorescent activated cell sorting (FACS). Transgenic mice expressing GFP under the control of the L7 promoter were used to purify live Purkinje cells (Tomomura et al, 2001). A knock-in of GFP into the Hoxa13 locus in mice was used to purify limb mesenchymal cells which were then used to show Hoxa13 null cells are defective in forming chondrogenic condensations in vitro (Stadler et al, 2001).…”
Section: 5b Gfp As a Marker For Cell And Tissue Typesmentioning
confidence: 99%